Layer, island and dendrite crystallizations of amorphous films as analogs of Frank-van der Merwe, Volmer-Weber and Stranski-Krastanov growth modes - Bagmut, A. G. (Scientific and Technological Corporation "Institute for Single Crystals", 2019)
Electron-microscope investigations in situ, concerning the crystallization of amorphous films, are systematized. Based on the analysis of the structure and morphology of crystals growing in amorphous films as a result of electron beam influence, a quantitative interpretation of layer polymorphic crystallization (LPC), island polymorphic crystallization (IPC) and dendrite polymorphic crystallization (DPC) is given. For each crystallization mode the parameter of dimensionless relative length δ₀, equal to the ratio of the characteristic length to the value, characterizing the size of the unit cell of the crystal, was respectively assigned. Based on the video recording of the process, the kinetic curves of LPC, IPC and DPC are constructed. LPC (Cr₂O₃, V₂O₃, Sb₂S₃, Se and others) is regarded as morphological analog of Frank-van der Merwe (FM) growth mode of a crystal from the vapor phase. In the case of LPC in the zone of observation in amorphous film grows a single flat crystal. By analogy with FM growth mode an energy criterion of the LPC can be written as σₐ≥ σ+ σₐc+ εd, where σₐ is the free energy of the amorphous phase-vacuum interface, σc is the free energy of the crystalline phase-vacuum interface, σac is the free energy of the amorphous-crystalline phase interface, and εd is the energy of deformation of the growing crystalline layer. For LPS the quadratic dependence of the fraction of the crystalline phase x on time t takes place and δₒ ~ 2500-4700. IPC (Al₂O₃, ZrO₂, Ni, Re and others) is regarded as morphological analog of Volmer-Weber growth mode of a crystal from the vapor phase. In the case of IPC in the zone of observation in amorphous film grows a lot of small disoriented crystals. By analogy with VW growth mode an energy criterion of the IPC can be written as σₐ ≤ σc + σₐc + εd. For IPS the exponential dependence of x(t) takes place and δₒ ~ 100-900. DPC (films of Fe-C, HfO₂) is regarded as morphological analog of Stranski-Krastanov growth mode of a crystal from the vapor phase. A characteristic sign of DPC is the formation of dendrite branches along the sides of a flat single crystal. For DPC the quadratic dependence of x(t) takes place and δₒ~ 3900.
Keywords: kinetic of crystallization; growth modes; in situ TEM; relative length; video recording